Antithrombotic Therapy after Bleeding in Elderly Polimorbid Patient: Our Time Challenge - M. R. Atabegashvili; M. Yu. Gilyarov; E. V. Konstantinova; A. N. Kostina; A. P. Nesterov; T. D. Pakharkova; A. E. Udovichenko (Рациональная фармакотерапия в кардиологии)
In recent years, there has been a clear trend towards an increase in the number of elderly patients suffering from several polymorbid diseases, which considerably complicates the forecast and tactics of management. A clinical case of an elderly patient, suffering for a long time from type 2 diabetes mellitus, receiving insulin and treated with programmed hemodialysis due to terminal chronic renal failure, and suffering from atrial fibrillation in permanent form, is presented. The patient was hospitalized in theCityClinicalHospital№1 named after N.I. Pirogov due to acute repeated myocardial infarction. An emergency percutaneous coronary intervention was performed, the infarct-dependent artery was stented with a drug-eluted stent. The postoperative period complicated by the development of acute blood loss associated with bleeding from the upper sections of the gastrointestinal tract, and severe anemia of the combined genesis (posthemorrhagic, renal). This situation required doctors to make non-standard decisions in the choice of antithrombotic therapy. This clinical case illustrates the difficulties in elderly polymorbid patient management in real clinical practice and the controversial issues arising in the prescribing the antithrombotic therapy, especially after bleeding had developed. The supporting guidelines cannot answer all the questions which the daily practice poses to the doctor. In each case, the resumption of antithrombotic therapy and its optimal choice for an elderly polymorbid patient with developed bleeding is the subject of discussion and presented a real challenge for the treating physician.